An Approach to the Galician Groups in Madrid during the First Thirty Years of the 20th Century: The so-called “Mocedade Céltiga” - Acuña, Ana (Madrygal. Revista de Estudios Gallegos, 2015)
This study will be centered on a group of Galicians formed around the figure of Fermín Penzol. This group, which adopted different names (Xuventude Céltiga, Irmandade Céltiga de Madrid, Mocedade Céltiga, Delegación da Irmandade Nazonalista Galega), existed from 1919 to 1926.
Keywords: Group of Galicians in Madrid; Fermín Penzol; Mocedade Céltiga